MAKING A QUALITY INSTITUTION BASED ON MANAGEMENT STANDARDS (SURVEY at MTSN 16 JAKARTA TIMUR) - Kunaenih Kunaenih (STIT AL-AMIN KREO TANGERANG, 2020)
The author's background in choosing this title is related to the facts in the field which show that there are still schools that have not been able to implement management standards maximally so that it has a negative impact on the quality and quality of these educational institutions. The purpose of this study is to analyze and further examine the quality of the institutions associated with management standards in a formal education institution, namely MTsN 16, East Jakarta. The data analysis method used in this study was conducted by interview and observation methods, because this study was included in qualitative research. The results of this study are MTsN 16 East Jakarta is one of the quality schools based on good management standards, because of the efforts made by the school, school principals and teachers to be able to manage the school system in various fields with good governance and cooperation. good.